TSUNAMI HAZARDS ASSOCIATED WITH THE PERACHORA FAULT AT EASTERN CORINTH GULF, GREECE - Tselentis G.-A.; Gkika F.; Sokos E. (My University, 2006)
We investigate the tsunami hazard associated with the Perachora fault at eastern Corinth Gulf, Greece. Realistic faulting parameters are used to model expected coseismic displacements of the seafloor. This study also investigates the effect that rupture complexity has on the local tsunami wave field. Several earthquake scenarios are used as initial conditions for tsunami stimulation either considering the numerous published constant slip models or taking into account the fault rupture complexity with the help of a realistic finite-extent k-2 stochastic kinematic source model with k-dependent rise time. The obtained results indicate that there is substantially more variation in the local tsunami wave field derived from the inherent complexity of the shallow fault zone than predicted by a simple elastic dislocation model. Rupture complexity, as represented by heterogeneous slip-distribution patterns, has an important effect on near-field tsunami records. Tsunami hazards assessments based on only a few scenario earthquakes may not accurately account for nutural variation in tsunami amplitude caused by earthquake rupture complexity.